Harnessing the Bohemian: Artists as innovation partners in rural and remote communities - Skippington, Peter (ANU Press, 2016)
HarnessingÂ theÂ BohemianÂ takes a fresh and interdisciplinary perspective on the intractable problem of shrinking populations and resources in remote/rural communities. It challenges the conventional wisdom of community development theories and practices and envisages more central roles for the creative disciplines in revitalising futures planning.Â It argues that the evolution of technologies, the emergence of creative economies, the increasing demand for creative products, and the emergence of new creative talent are continually changing community expectations and opportunities. Consequentially, fresh arguments and new ideas must be developed to stimulate more creative and innovative approaches to community development. Recognising that creativity and innovation exist across all community sectors, this book proposes practical new approaches that harness the creative capital of all community stakeholders.